Morpho-functional state of human fetuses' adrenal cortex during influence of maternal infection - Vira Tovazhnianska (Kazimierz Wielki University, 2018)
Aim of study. To reveal influence of maternal infection on morpho-functional state of fetuses' adrenal cortex. Methods. The material was obtained during sectional studies, which were conducted on the basis of the "Kharkiv Regional Clinical Perinatal Center" from 2012 to 2016. The sample included fetuses with a gestation period of 32-42 weeks. The adrenal glands of fetuses were examined morphologically, using histological, morphometric and immunohistochemical methods. Results. It was found that maternal infection leads to a decrease of morpho-functional activity of constant and fetal zones of the adrenal cortex, which was manifested by hypoplasia of zona glomeroulosa and fetal zone depletion; cytolysis and resorption of spongiocytes in zona fasciculata. In this case, increase in hormonal production in the permanent cortex is a manifestation of compensatory-adaptation reaction.